Neural Correlates of Freezing of Gait in Parkinson's Disease: An Electrophysiology Mini-Review - Marquez, J. Sebastian; Hasan, S. M. Shafiul; Siddiquee, Masudur R.; Luca, Corneliu C.; Mishra, Virendra R.; Mari, Zoltan; Bai, Ou (Frontiers in Neurology, 2020)
Freezing of gait (FoG) is a disabling symptom characterized as a brief inability to step or by short steps, which occur when initiating gait or while turning, affecting over half the population with advanced Parkinson's Disease (PD). Several non-competing hypotheses have been proposed to explain the pathophysiology and mechanism behind FoG. Yet, due to the complexity of FoG and the lack of a complete understanding of its mechanism, no clear consensus has been reached on the best treatment options. Moreover, most studies that aim to explore neural biomarkers of FoG have been limited to semi-static or imagined paradigms. One of the biggest unmet needs in the field is the identification of reliable biomarkers that can be construed from real walking scenarios to guide better treatments and validate medical and therapeutic interventions. Advances in neural electrophysiology exploration, including EEG, and DBS, will allow for pathophysiology research in more real-to-life scenarios for better FoG biomarker identification and validation. The major aim of this review is to highlight the most up to date studies aiming to explain the mechanisms underlying FoG through electrophysiology explorations. Secondly, the latest methodological approaches used in the neurophysiological study of FoG are summarized, and the potential future research directions are discussed.